Component composition of volatile organic substances of dog-rose petals - О. Л. Рубцова; І. В. Коваль; Н. І. Джуренко; О. П. Паламарчук (Plant Varieties Studying and Protection)
Purpose. To analyse the qualitative and quantitative composition of volatile organic substances (VOS) in the petals of six species of dog-rose in the collection of M. M. Gryshko National Botanic Garden of the NAS of Ukraine for further breeding.